Control of muscle tone in the human colon. - Steadman, C J (1992)
Human colonic muscle tone varies diurnally and postprandially in predictable ways. Increased tone reduces the capacity of the colon to store contents after a meal, whereas increased distensibility (lesser tone) during sleep enlarges the storage capabilities and may slow transit. We tested the hypothesis that antidiarrhoeal drugs would also alter tone which, in turn, might reduce diarrhoea by facilitating the storage and salvage of fluids. Using a colonic barostat to create low pressure, isobaric colonic distension in healthy volunteers, we found that intravenous atropine (0.01 mg/kg) relaxed the colon during fasting, reduced the postprandial increase in tone, and enhanced relaxation in the late (1-2 hour) postprandial period. Intravenous morphine (0.1 mg/kg) caused variable effects soon after injection but, in fasting subjects, the descending colon relaxed 70-90 minutes after morphine. These changes in colonic motility were not always obvious by conventional manometric recording. Colonic distensibility is increased by antidiarrhoeal drugs and this effect may contribute to their efficacy in slowing colonic transit and augmenting absorption.